(untitled) (Journal of Partial Differential Equations, 2022)
The purpose of this paper is to investigate the nonexistence of positive solutions of the following doubly nonlinear degenerate parabolic equations: align*cases ut= abla_k · ( u^m-1| abla_k u |^p-2 abla_k u )+V(w)u^m+p-2 ,& in Ω × (0,T), u(w,0)=u_0 (w)0, & in Ω , u(w,t)=0, & on Ω × (0,T), cases align* where Ω is a Carnot-Carathéodory metric ball in R^2n+1 generated by Greiner vector fields, VL_loc^1 (Ω ), kN, mR, 1